Protein hydrolysis of eggs from the sea urchin Tripneustes gratilla by the industrial enzyme alcalase - Hoa, Dinh Thi Kim; Bich, Hoang Thi; Long, Pham Quoc; Toan, Tran Quoc; Phuong, Doan Lan (Vietnam Journal of Science and Technology, 2019)
ABSTRACT – HCTN 82         The demand for the aquatic products has increased worldwide. In many cases, natural fisheries are overexploited and unable to satisfy the expanding market. Essential efforts to develop marine aquaculture, particularly for high value products, are encouraged and supported by many countries. Sea urchin is an invertebrate member of the phylum Echinodermata of marine animals living on the ocean floor. Recent years it has become increasingly important because of its economic potential, nutritional value and medicinal properties. The objective of this report is to build a process for increasing the value of egg of sea urchin Tripneustes gratilla (Linnaeus, 1758) collected in Hon Tam, Nha Trang, Khanh Hoa, Viet Nam in 2016. In this report, the industrial enzyme alcalase was used to hydrolysis protein to low quantity protein such as amino acids, oligopeptides that are considered as the valuable source of food.Keywords : Tripneustes gratilla, amino acids, hydrolysis, low quantity protein, sea urchin